Geometric morphometric analysis of Arius manillensis and Arius dispar (Siluriformes Ariidae) Populations in Laguna de Bay, Philippines. - Santos, Brian S.
Geometric morphometrics has become a widely used tool in studying shape variation in fish populations. In this study, geometric morphometrics was used to examine shape variation in the sea catfishes. Arius manillensis and A. dispar. The endemic species A. manillensis and the native species A. dispar constitute major fishery resources in Laguna de Bay. Thus, they are economically important species. The two species look very similar externally, but they can be distinguished by examining the tooth patch morphology on the palate. However, within each species, there are variants of tooth patch morphology. Shape differences between A. manillensis and A. dispar, between populations, and between variants within each species, were determined. Samples were obtained from Binangonan, Tanay, and Calamba areas of Laguna de Bay. Shape differences between species, between morphs within species and among specimens of different sites were significant, but the groups were difficult to differentiate due to high overlaps in Canonical Variate Analysis (CVA) plots and low Mahalanobis distance-based correct classification percentages. This was attributed to possible introgression between A. manillensis and A. dispar.
Keywords: Arius dispar; Arius manillensis; Geometric morphometrics; Kanduli; Laguna de Bay; Siluriformes